Functional genetic diversity in popcorn lines (Zea mays L. var. Everta) focusing on productivity through SSR-EST markers - Lavínia Santana Ladeira Gomes; Marcelo Vivas; Alex Souza Rodrigues; Lilia Marques Gravina; Ramon de Moraes; Rafael Nunes de Almeida; Helaine Christine Cancela Ramos; Antônio Teixeira do Amaral Júnior (Acta Scientiarum. Agronomy, 2026)
Popcorn is a distinct type of maize with a high market demand. In Brazil, there is a shortage of national cultivars that meet production and marketing needs, so seeds are imported, hindering the growth of this sector. Nevertheless, its cultivation is important and can be enhanced with investments in genetic improvement aimed at optimizing characteristics such as productivity. Molecular markers support this type of research: They allow the genetic characterization of lines and inferences about genetic variability. Microsatellites such as simple-sequence repeats (SSRs) are widely used in genetic studies due to their high reproducibility and polymorphism. SSR-expressed sequence tag (EST) markers are microsatellites related to transcribed sequences. Functional variability is linked to the maximization of genetic gains, making the study of these regions valuable. In this context, the present study used SSR-EST markers to characterize the productivity of 47 popcorn lines from the UENF Germplasm Bank, selected for their high performance in previous studies. Young leaves of the lines were collected for DNA extraction, which was used for polymerase chain reaction (PCR) with 30 preselected primers. The amplified material was subjected to capillary electrophoresis for identification and separation of alleles. The data were converted into a dissimilarity matrix, which allowed for the estimation of diversity metrics such as the number of alleles, the polymorphic information content, observed heterozygosity, expected heterozygosity, and the inbreeding coefficient. A total of 94 distinct alleles were detected, with an average of 3.13 alleles per locus, indicating that, although the lines present high levels of allelic fixation and inbreeding, they retain moderate genetic variability for population configuration. A dendrogram created using unweighted pair group method using arithmetic mean revealed an optimal number of six populations. This information provides indications of specific genotypes for crosses that can maximize heterosis in hybridizations to support the improvement program.